2011
DOI: 10.1073/pnas.1019330108
|View full text |Cite
|
Sign up to set email alerts
|

Multiple recognition assay reveals prostasomes as promising plasma biomarkers for prostate cancer

Abstract: Prostasomes are microvesicles (mean diameter, 150 nm) that are produced and secreted by normal and malignant prostate acinar cells. It has been hypothesized that invasive growth of malignant prostate cells may cause these microvesicles, normally released into seminal fluid, to appear in interstitial space and therewith into peripheral circulation. The suitability of prostasomes as blood biomarkers in patients with prostate cancer was tested by using an expanded variant of the proximity ligation assay (PLA). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
179
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(188 citation statements)
references
References 51 publications
2
179
0
7
Order By: Relevance
“…Moreover, there is an increasing expectation in their potential use as clinical targets and as diagnostic and prognostic biomarkers since vesicles occur in bloodstream and other biological fluids (e.g., urine, semen, amniotic fluid, saliva, synovial and bronchoalveolar fluid, breast milk, spinal fluid, ascites, malignant and pleural effusion), particularly the ones that are exposed to primary tumors (2,19,(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is an increasing expectation in their potential use as clinical targets and as diagnostic and prognostic biomarkers since vesicles occur in bloodstream and other biological fluids (e.g., urine, semen, amniotic fluid, saliva, synovial and bronchoalveolar fluid, breast milk, spinal fluid, ascites, malignant and pleural effusion), particularly the ones that are exposed to primary tumors (2,19,(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the EV concentration present in serum of tumor-bearing patients was shown to be increased compared to healthy controls [217,[232][233][234][235]. The EV protein abundance also has prognostic value as it was observed that patients with stage III melanoma with a high EV-associated TYRP2 protein burden showed increased risk of disease progression [207].…”
Section: 2evs As Biomarkermentioning
confidence: 96%
“…Moreover, following resection of the primary tumor, the EV concentration markedly decreased indicating its correlation with tumor presence [235]. However, relying solely on EV concentration lacks specificity as the same observation was made for distinct cancer types [217,[232][233][234][235] and, importantly, for non-disease stimuli (e.g. physical exercise [236]).…”
Section: 2evs As Biomarkermentioning
confidence: 99%
“…Prostasomes are not only secret by normal prostatic cells but also by neoplastic cells that export prostasomes to the extracellular environment, participating in tumor proliferation and metastasis [49]. Prostasome levels are reportedly increased in prostate cancer patients and these levels are associated with the disease aggressiveness [50]. The development of future isolation techniques for prostasomes found in biological fluids will let to get better insight in the identification and analysis of the protein, lipid and nucleic acids content of them and the potential utility for the diagnosis and prognosis of prostate cancer.…”
Section: Exosomes and Prostasomesmentioning
confidence: 99%